Yield mapping system for vegetables picked up with a tractor-pulled platform - Saldaña, N.=700 1 Cabrera, J.M.; Serwatowiaki, R.J.; Gracia, C.
(Es, En)
ilus., 9 ref.
Keywords: AGRICULTURA; COSECCHA; RECOLECCION DE DATOS; RENDIMIENTO DE CULTIVOS; HORTALIZAS; ESPAÑA; MAPEO DE RENDIMIENTO